PENGARUH PERENCANAAN ANGGARAN, PENCATATAN ADMINISTRASI, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENYERAPAN ANGGARAN (STUDI PADA OPD PROVINSI RIAU) - Putra Bayu Farhan; Kennedy Kennedy; Zarefar Arumega (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The financial realization number and physical of the Riau Regional Budget are still low because the absorption capacity has only reached 68.2% and physically 75% of the target that should have been achieved at least 90%. Several different variables have been tested by several previous researchers associated with budget absorption. The purpose of this study was to test the correlation of 3 (three) independent variables, namely variable x (budget planning, administrative records and human resource competence) with 1 (one) dependent variable, namely variable y (budget absorption) in OPD Riau Province using 3 (three) hypotheses. The method used in this study is a survey method with the respondent is the head of the department / agency, treasurer of expenditure and head of department in OPD Riau Province. The survey was conducted for 52 (fiftytwo) days with a participation rate of 82.72%. The data were processed and analyzed using SPSS version 25. The data were analyzed to test the hypothesis using multiple linear regression analysis. The results of this study indicate that budget planning, administrative records, and human resource competence affect budget absorption.Keywords: Budget Planning, Administrative Records, Competency Of Human Resources, Budget Absorption.